The ERCC1-4533/8092, TNF-α 238/308 polymorphisms and the risk of hepatocellular carcinoma in Guangxi Zhuang populations of China: Case-control study. Issue 44 (November 2016) - Li, Yanqiu; Ou, Chao; Shu, Hong; Zhao, Huiliu; Zhu, Bo
Abstract: Objective: To investigate the relationship between excision repair cross-complementing group 1 (ERCC1)-4533/8092, tumor necrosis factor-alpha (TNF-α)-238/308 polymorphisms, and the risk of hepatocellular carcinoma (HCC) in Guangxi Zhuang population of China. Methods: Polymerase chain reaction-restriction fragment length polymorphism method was used to detect the ERCC1-4533/8092 and TNF-α-238/308 polymorphisms in 88 cases with HCC and 82 cases of normal control. Results: There were no differences in the frequency distribution of ERCC1-4533 and TNF-α-238 polymorphisms in the HCC group and the control group ( P > 0.05). The genotype frequency distributions of the ERCC1-8092 and TNF-α-308 in the HCC group and the control group were different ( P < 0.05). Compared with ERCC1-8092 CC genotype, ERCC1-C8092 CA/AA genotype had higher risk of HCC (CA/AA vs CC; odds ratio 3.51, 95% confidence interval 1.03–12.016 ) . Compared with TNF-α-308 GG genotype, TNF-α-308 GA/AA genotype was significantly associated with an increased risk of HCC (GA/AA vs GG; odds ratio 3.84, 95% confidence interval 1.011–14.57). Conclusion: The genetic polymorphisms of ERCC1-8092 and TNF-α-308 are associated with the risk of HCC in Guangxi Zhuang population of China.